2020
DOI: 10.11591/ijphs.v9i4.20546
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutritional status on Rohingya under-five children in Bangladesh

Abstract: The extent of nutritional status affecting Rohingya refugee under-five children has become a major health issues in Bangladesh. This study aimed to investigate the nutritional status and its effect on under-five Rohingya children in comparison with the areas of Bangladesh. A cross-sectional study of 300 under-five children were conducted by structured questionnaire from Rohingya camp (100), Cox’s Bazar (100) and Dumki (100) applying simple random method. Anthropometric indices (weight, height, mid-upper arm ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…Grey literature searching retrieved 30 reports of which 23 met eligibility criteria. In total, 33 reports were included in the review 24–56 Figure 1. shows the search process using the PRISMA flow diagram template 16…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Grey literature searching retrieved 30 reports of which 23 met eligibility criteria. In total, 33 reports were included in the review 24–56 Figure 1. shows the search process using the PRISMA flow diagram template 16…”
Section: Resultsmentioning
confidence: 99%
“…This means we could not assess the risk of misclassification bias or the consistency and appropriateness of data collection methods. One study was of poor quality with a score of 2, suggesting a higher risk of bias, due to a lack of clarity in several areas including the number of participants in the study 44. These scores suggest that, overall, the studies were of moderate to high quality, so we can have a good degree of confidence in the evidence that they provide.…”
Section: Resultsmentioning
confidence: 99%
“…It will reinforce the school practices and will lead to reduced incidences of problems of over and undernutrition [34]. Also, in the recent years it is observed that there is a rise in the cases of stunting which is easily preventable by paying attention to the nutrition of children [35]. All those involved in handling food must have sufficient knowledge and must implement best hygiene practices [36] at meal times to ensure that healthy practices are taught to the toddlers.…”
Section: Resultsmentioning
confidence: 99%
“…The plight of the Forcibly Displaced Myanmar Nationals (FDMN) community in Bangladesh has been one of the most violent and protracted humanitarian crises in recent history, marked by restricted mobility, denial of citizenship, forcible displacements, and decades-long persecution ( 1 ). Violence erupted in Myanmar in the late 1970s, resulting in the displacement of millions of FDMN from its Rakhine state to Bangladesh ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Violence erupted in Myanmar in the late 1970s, resulting in the displacement of millions of FDMN from its Rakhine state to Bangladesh ( 2 ). Currently, more than 1.1 million FDMN are residing in Bangladesh ( 1 ) and housed mostly in overcrowded settlements in the Ukhiya and Teknaf Upazilas of the Cox’s Bazaar district. More than 180,000 children under the age of five in this population ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%